Determinación de anticuerpos anti-péptido citrulinado y su relación con el el factor reumatoide para la detección temprana de artritis reumatoide en los adultos mayores del Ancianato Daniel Álvarez Sánchez de la ciudad de Loja. - Castillo Rosales, Carmen Gladys (2016)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by the destruction and inflammation of the joints, causing malfunction of the same. It affects between 1 and 2% of the world's population, women being the most affected. (López, M., Urbano, A., Cárdenas. M., Osuna, A., Lendínez, M. 2012). The tests most commonly used for the diagnosis of AR are Rheumatoid Factor and antibody test cyclic antipeptidos citrulinados (Anti - CCP), reason why this so-called study arose: DETERMINATION OF ANTIBODIES TO CITRULLINATED PEPTIDE AND ITS RELATIONSHIP WITH RHEUMATOID FACTOR FOR EARLY DETECTION OF RHEUMATOID ARTHRITIS IN THE ELDERLY IN THE NURSING HOME DANIEL ALVAREZ SANCHEZ OF THE CITY OF LOJA. The study was descriptive of cross-cutting, taking as shown in 56 people who met the criteria of inclusion, that blood samples analysis is performed using the test of the FR by agglutination technique and the determination of Anti-CCP using Elisa inmunoenzimoanalisis, obtained the following results: Anti-CCP positive (16) % and 34% positive FR 29 (19). Relating the two tests were obtained: Anti-CCP and positive FR 18% (10), Anti-CCP positive and FR negative 11% (6), Anti-CCP negative and positive FR 16% (9) and Anti-CCP negative and negative FR 55% (31). Keywords: rheumatoid arthritis, rheumatoid factor, anti-citrullinated peptide antibodies.